The Complete Mitochondrial Genome of a Neglected Breed, the Peruvian Creole Cattle (Bos taurus), and Its Phylogenetic Analysis - Arbizu Berrocal, Carlos Irvin (2022)
Cattle spread throughout the American continent during the colonization years, originating creole breeds that adapted to a wide range of climate conditions. The population of creole cattle in Peru is decreasing mainly due to the introduction of more productive breeds in recent years. During the last 15 years, there has been significant progress in cattle genomics. However, little is known about the genetics of the Peruvian creole cattle (PCC) despite its importance to (i) improving productivity in the Andean region, (ii) agricultural labor, and (iii) cultural traditions. In addition, the origin and phylogenetic relationship of the PCC are still unclear. In order to promote the conservation of the PCC, we sequenced the mitochondrial genome of a creole bull, which also possessed exceptional fighting skills and was employed for agricultural tasks, from the highlands of Arequipa for the first time. The total mitochondrial genome sequence is 16,339 bp in length with the base composition of 31.43% A, 28.64% T, 26.81% C, and 13.12% G. It contains 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and a control region. Among the 37 genes, 28 were positioned on the H-strand and 9 were positioned on the L-strand. The most frequently used codons were CUA (leucine), AUA (isoleucine), AUU (isoleucine), AUC (isoleucine), and ACA (threonine). Maximum likelihood reconstruction using complete mitochondrial genome sequences showed that the PCC is related to native African breeds. The annotated mitochondrial genome of PCC will serve as an important genetic data set for further breeding work and conservation strategies.